1983
DOI: 10.1093/carcin/4.12.1583
|View full text |Cite
|
Sign up to set email alerts
|

The role of highly purified cytochrome P-450 isozymes in the activation of 4-aminobiphenyl to mutagenic products in the Ames test

Abstract: The role of cytochromes P-450 and P-447 in the activation of 4-aminobiphenyl to mutagens in the Ames test was studied using S9 preparations and highly purified isozymes. S9 preparations from beta-naphthoflavone-pretreated rats were more efficient in converting 4-aminobiphenyl to mutagens than the corresponding preparations from phenobarbitone-pretreated animals. Similarly, reconstituted systems comprising purified cytochrome P-447 were twice as efficient as cytochrome P-450 in activating the carcinogen. Of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The present paper describes a unique cytosolic oxygenase activity, apparently of high specific substrate specificity, which is effective in activating certain aromatic amines to mutagenic intermediates in the Ames test. As ringhydroxylated products are largely non-mutagenic [14,15] it may be inferred that this enzyme catalyses the N-hydroxylation of the amine. The requirements for oxygen and reduced dinuc1eotides also support such a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present paper describes a unique cytosolic oxygenase activity, apparently of high specific substrate specificity, which is effective in activating certain aromatic amines to mutagenic intermediates in the Ames test. As ringhydroxylated products are largely non-mutagenic [14,15] it may be inferred that this enzyme catalyses the N-hydroxylation of the amine. The requirements for oxygen and reduced dinuc1eotides also support such a role.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Cofactor requirement differs in that NADH can c1early support the microsomal but not the cytosolic activation of 2-aminofluorene. (b) The Aroc1or 1254-induced cytosol failed to convert 4-aminobiphenyl and benzidine to mutagenic intermediates, which are, however, activated by the microsomes [7, 14,16]. It is worth pointing out that 2-aminoanthracene, frequently used as a positive control in mutagenicity studies, is also extensively metabolised by hepatic cytosolic fractions [17].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that rubber workers also had increased risk for bladder cancer, attributed largely to exposure to aromatic amines [241,242]. Most aromatic amines are initially activated by Nhydroxylation, mainly in the liver via a cytochrome P-450 catalyzed reaction [243,244].…”
Section: Aromatic Amines and Amidesmentioning
confidence: 99%
“…4′-OH-ABP binding to DNA is consistent with this metabolite being mutagenic and/or genotoxic. However, while ABP was shown to be mutagenic in the Ames test supplemented with a cytochrome P-450 activation system, 4′-OH-ABP was not mutagenic (57). That is, 4′-OH-ABP was not activated by cytochrome P-450.…”
Section: Discussionmentioning
confidence: 95%